Exploration of Misconceptions about Virus Material Based on Gender among High School Students in Malang - Pitaloka, Karin Anindita Widya; Mahanal, Susriyati; Prabaningtyas, Sitoresmi (Jurusan Pendidikan Biologi - Universitas Siliwangi, 2024)
High school students must comprehend the notion of viruses since the application of principles found in virus content is tied to everyday conduct. Pupils continue to have misconceptions regarding viruses because they mistakenly believe that they are cells. This study aims to investigate the causes of misconceptions about virus material among Malang high school students by analyzing the misconceptions depending on gender. A four-tier diagnostic multiple-choice test was the tool utilized. The five decision categories on a four-tier diagnostic multiple-choice test are scientific conception, ignorance, false positive, false negative, and misperception. In this study, purposeful random sampling was combined with a survey method. Four hundred and seventy-seven Malang high school students who have studied virus material made up the sample for this study. Using an independent sample T-test, descriptive quantitative data analysis was the method employed. The four-tier diagnostic multiple-choice test was found to be reliable (0.835) and valid (0.411-0.767) in terms of value range. The findings indicated that male and female students had different percentages of misconceptions 56.1% and 43.9%, respectively. Independent sample T-test findings yielded a significant value of 0.017(0.05) suggests that there is a substantial discrepancy in the beliefs held by male and female students.